Beispiel Nr: 05
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ -1x^3+4x =0\\ \\ \textbf{Rechnung:} \\ x(-1x^2+4)=0 \Rightarrow x=0 \quad \vee \quad-1x^2+4=0\\ -1x^2+4 =0 \qquad /-4 \\ -1x^2= -4 \qquad /:\left(-1\right) \\ x^2=\displaystyle\frac{-4}{-1} \\ x=\pm\sqrt{4} \\ x_1=2 \qquad x_2=-2 \\ \underline{x_1=-2; \quad1\text{-fache Nullstelle}} \\\underline{x_2=0; \quad1\text{-fache Nullstelle}} \\\underline{x_3=2; \quad1\text{-fache Nullstelle}} \\$